Expression of pluripotency markers in the bovine uterus with adenomyosis. Issue 1 (December 2015) - Łupicka, Martyna; Socha, Barbara; Szczepańska, Agata; Korzekwa, Anna
Abstract Background Adenomyosis is a proliferative uterine dysfunction with unknown aetiology. One possible mechanism of its development involves disturbances in stem cell differentiation in uterine tissue. Previously, we identified pluripotent/multipotent cells in the bovine uterus, therefore our present study focused on determining expression of pluripotency markers, NANOG, OCT4 and SOX2, in bovine adenomyotic tissues and cells. Findings Immunolocalisation revealed protein expression of NANOG, OCT4 and SOX2 in both normal and adenomyotic uteri. mRNA expression forNANOG andOCT4 was increased in tissues obtained from uteri with adenomyosis compared to controls, but at the protein level there were no significant differences. mRNA expression for all three pluripotency markers was higher in myometrial cells isolated from uteri with adenomyotic lesions than in those isolated from normal uteri. The protein level of NANOG and SOX2 was decreased in stromal cells from adenomyotic tissues, whereas the level of OCT4 and SOX2 was increased in myometrial cells obtained from dysfunctional uteri. Conclusions The results indicate significant changes in expression of pluripotency markers in adenomyotic compared to normal uteri, which suggest the involvement of uterine stem cells in adenomyosis.